O emprego da metodologia ativa Peer Instruction aliada ao GeoGebra no ensino da geometria na educação básica - Batista, Joacildo Pimentel (2024)
In this research, our objective was to evaluate the feasibility of employing the active methodology Peer Instruction combined with GeoGebra in teaching certain topics of Geometry in Elementary Education. We conducted out research with a class oh 9th grade students at Colégio Militar de Santa Maria, consisting of 30 students, over a period of 3 weeks, totaling 15 class hours. At the end, we administered a partial assessment (1st AP2). The activities focused on plane geometry, specifically covering the topics of the Thales’ Theorem and the Angle Bisector Theorem. We utilized GeoGebra to demonstrate the angle Bisector Theorem and observed that using this tool in the classroom facilitated a deeper understanding of the theorems, promoting learning. Additionally, we adopted the Moodel platform to support studying outside of the school environment, given the necessity for preparatory study to carry out the planned activities in the classroom. We grounded our approach in the Theory of Meaningful Learning to justify our proposal. We conducted a search in the PROFMAT dissertations database for dissertations related to our proposal to verify existing work, finding only one study that addressed the active Methodology Peer Instruction. We report on the classroom experiences and present the results of conceptual tests, student opinion surveys, and the final partial assessment administered at the end of the classroom activities. The results were very satisfactory and encouraging, demonstrating the validity and effectiveness of the applied methodology and leading us to conclude that the use of active methodology peer instruction is suitable for elementary education, particularly when combined with GeoGebra.